Sulfone Based-Electrolytes for Lithium-Ion Batteries: Cycling Performances and Passivation Layer Quality of Graphite and LiNi1/3Mn1/3Co1/3O2 Electrodes. Issue 7 (10th January 2020) - Flamme, Benjamin; Światowska, Jolanta; Haddad, Mansour; Phansavath, Phannarath; Ratovelomanana-Vidal, Virginie; Chagnes, Alexandre
Abstract : The solvent 3-methoxytetrahydrothiophene 1, 1-dioxide (MESL) was synthesized and its cycling performances of grapshite and LiNi1/3 Mn1/3 Co1/3 O2 (NMC) electrodes were investigated in view of the high anodic stability of MESL in the presence of lithium bis-trifluoromethanesulfonimidate (LiTFSI). Galvanostatic charge-discharge of graphite electrode was possible in MESL + LiTFSI (1 M) only in the presence of 5% (vol.) fluoroethylene carbonate (FEC) at 40 °C. On the other hand, a good cycling ability of NMC electrode with this electrolyte was observed at room temperature even at a cut-off voltage of 4.5 V vs Li + /Li. However, it was necessary to reduce the cut-off voltage from 4.5 V to 4.3 V vs Li + /Li in order to keep a good cycling ability <<< when the temperature was increased from 25 °C to 40 °C due to an exaltation of oxidation reactions onto the cathode surface. X-Ray Photoelectron Spectroscopy (XPS) analyses were performed to investigate the electrode/electrolyte interphase and formation of passive layer on the electrode surfaces in order to explain the differences of cycling ability of NMC and graphite electrodes at room temperature and 40 °C.